Net-Baryon Production in Nucleus-Nucleus Collisions and Rare QGP Events. (April 2015) - Arakelyan, G H; Merino, C; Shabelski, Yu M
Abstract: The experimental data on net proton and net Λ-hyperon spectra obtained by the NA35 Collaboration, as well as the inclusive densities of Λ and obtained by NA49, NA57, and STAR collaborations, are compared with the predictions of the Quark-Gluon String Model. The contributions of String Junction diffusion, interactions with nuclear clusters, and percolation corrections are accounted for. The level of numerical agreement of the calculations with the experimental data is of about 20-30%. We also consider the experimental ratios of multistrange to strange antibaryon production. The significant differences between the experimental and, especially, values and the QGSM predictions can be interpreted as the signal of the existence of an additional source of multistrange antibaryon production.